COMPUTER ASSISTED INTERPRETER TRAINING FOR STUDENTS WHO ARE NOT FOREIGN LANGUAGE MAJORS - CHEN, Sheng-jie (Comparative Legilinguistics, 2010)
The aim of the existing case study was to investigate the implications of applying computers to teaching interpreting to students who were not foreign language majors. Some researchers argued that interpreting courses are very difficult, so they should be offered to qualified post-graduate students instead of undergraduate students. However, most undergraduate programs in Taiwan offer interpretation courses. In addition, in China two-semester interpreter training courses have even been offered to most undergraduate students who were not foreign language majors. Furthermore, computers have been widely used in interpreter training, but no research has been available that investigated how to apply computer assisted interpreter training (CAIT) to teaching interpreting to students who are not foreign language majors. Qualitative research methods have been used to collect and analyze the data to complete the report in this study. Participants consisted of the author and the 18 students, who were not foreign language majors, taking a computer assisted interpreter training course that the author offered in a university in Taipei, Taiwan, in 2009. The results of the study indicated that CAIT may be developed into IM (the interpretation method) of foreign language teaching to teach students who are not foreign language majors.